Pengaruh Literasi Keuangan Syariah Dan Motivasi Terhadap Tingkat Frugal Living Pada Konsumen Gen Z Di Era Non Tunai - Asep Nur Imam Munandar; Deti Nuryaningsih; Puti Khairani Rijadi (CV. ITTC INDONESIA, 2025)
The increasing shift toward non-cash transactions among Generation Z has raised new challenges in maintaining frugal financial behavior aligned with Islamic values. This study aims to analyze the influence of Sharia financial literacy and motivation on the level of frugal living among Muslim Generation Z consumers in Bekasi. Using a quantitative approach with an explanatory research design, data were collected through questionnaires distributed to 96 respondents selected via simple random sampling. The analysis was conducted using SmartPLS with hypothesis testing through the bootstrap resampling method and t-statistics. The findings reveal that the R-square value for frugal living is 0.507, indicating that 50.7% of its variation is explained by Sharia financial literacy and motivation. Sharia financial literacy shows no significant effect on frugal living (p = 0.325; t = 0.984), while motivation demonstrates a highly significant positive effect (p = 0.000; t = 3.970). These results suggest that internal motivation plays a more dominant role than financial literacy in shaping frugal behavior among Generation Z in the non-cash transaction era.